Pengaruh Karakteristik Komite Audit Dan Ukuran Perusahaan Terhadap Financial Distress - Rega Dwi Putra; Vanica Serly (Jurnal Eksplorasi Akuntansi, 2020)
The purpose of this study was to analyze the effect of audit committee size, audit committee independence, audit committee meeting frequency, audit committee competence and company size on financial distress. The data in this study are annual reports of BUMN companies in Indonesia registered at the Ministry of BUMN in 2014-2018. The sampling method using purposive sampling method obtained by a sample of 180 companies. Testing the hypothesis in this study using multiple linear regression analysis. The results of his research are the independence of the audit committee, the frequency of audit committee meetings, and the competence of the audit committee has no effect on financial distress. Meanwhile, the size of the audit committee and the size of the company affect financial distress